sFLT1 in preeclampsia: trophoblast defense against a decidual VEGFA barrage? - S. Lee Adamson (The Journal of Clinical Investigation, 2014)
Preeclampsia, a life-threatening complication of human pregnancy, has a spectrum of clinical signs and is likely caused by an array of pathological mechanisms. However, elevated levels of soluble fms-like tyrosine kinase-1 (sFLT1) in the placenta and in the maternal circulation has emerged as a common finding in women with preeclampsia and likely is a causative factor in this disorder. In this issue of the JCI, Fan and colleagues provide experimental evidence from both humans and mice that suggests placental trophoblast cells overexpress sFLT1 in self defense against excessive VEGFA produced by maternal decidual cells. The authors’ work thus implicates the decidual cells of the mother as the culprit responsible for increased placental expression of sFLT1, a VEGFA antagonist that enters the maternal circulation and consequently induces the clinical signs of preeclampsia.